Anagrelide hydrochloridefor essential thrombocythemia. (December 2013) - Besses, Carles
<x xml:space="preserve">Abstract</x> Introduction: Essential thrombocytemia (ET) is a myeloproliferative neoplasm characterized by an elevated platelet count and an increased risk of thrombohemorrhagic events. <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Anagrelide hydrochloride&logicalOpe1=OR&field2=articletitle&text2=Anagrelide hydrochloride&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Anagrelide hydrochloride (AG) is an imidazolequinazoline derivative that inhibits bone marrow megakaryocytopoiesis, and this activity underlies the use of the drug in reducing the high platelet count in ET. In Europe, AG was licensed by the European Medicines Agency in 2004. Areas covered: An overview of the unmet medical needs of currently available therapies for ET and the rationale of AG in the management of this condition is presented. Salient features of the mechanism of action of AG, data on clinical efficacy including Phase I – III studies and randomized controlled clinical trials are reported. Safety and tolerability issues are also reviewed. Expert opinion: AG is being used in Europe as a second- or further-line treatment in high-risk ET patients that do not tolerate or are refractory to their current therapies; but in real life, there is some off-label use of AG as a first-line drug. There are still uncertainties in the treatment of ET, such as the definition of the response criteria and the end points of clinical relevance for future studies.